A badly-steered educational system? - Batanaz Palomares, Luis (Avances en Supervisión Educativa, 2008)
The recently-published PISA Report (Program for International Student Assessment) has provoked in Spain all kinds of reflections about the situation of our Educational System, only bound to air out vested interests lines of arguments by political parties, the Government itself, different associations and lobbies. However, its basic principles prove that the PISA Report does not intend to criticise any educational system, nor set a rank according to higher or lower achievements, but provide some global data that could be of use for reflection and the search of improvement.